Perfil econômico do lítio nos países sulamericanos e consumo mundial - Mendes, Marina Tietz de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The lithium industry has changed and the producers of lithium carbonate form South America play a dominant role in the world. This paper discusses the South American geological resources, production and producers of lithium considering the potential growth in lithium consumption for electric vehicle batteries. Taking into account the manufacturing companies and their external connections, their participation in corporate groups and the international market for the stocks of metal, in addition to facts and updates that affect this market and its key growth trends. This inventory of the most important reserves takes into account the geological context of the formation of these deposits, including a description of the types of deposits exploited in the world today. Besides the general description was made a brief description of the South American resources, more exploited by the media (Salar de Atacama, Salar de Hombre Muerto, Salar de Uyuni) and Pegmatites of Província Pegmatítica Oriental do Brasil and Província Seridó-Borborema).

Neste trabalho é feito estudo do mercado produtor de lítio na América do Sul, levando em consideração as empresas produtoras e suas conexões externas, sua participação em grupos corporativos, sua participação no mercado internacional em relação as reservas deste metal. Além de fatos e atualidades que interferem neste mercado e suas principais tendências de crescimento. Esse inventário das reservas mais importantes leva em consideração o contexto geológico da formação destes depósitos, incluindo a descrição dos principais tipos de depósitos explorados hoje no mundo. Além da descrição geral foi feita, uma breve descrição das reservas sulamericanas exploradas ou mais comentadas pela mídia (Salar do Atacama, Salar de Hombre Muerto, Salar de Uyuni) e Pegmatitos das províncias Pegmatítica Oriental do Brasil e Província Seridó-Borborema.
Keywords: Geologia economica; Economia mineral; Pegmatitos litiníferos; Salares; Lithium; Pegmatites; South American resources